Searching for the Haplorrhine Heterotherm: Field and Laboratory Data of Free-Ranging Tarsiers - Welman, Shaun; Tuen, Andrew A.; Lovegrove, Barry G. (Frontiers in Physiology, 2017)
The observation of heterothermy in a single suborder (Strepsirrhini) only within the primates is puzzling. Given that the placental-mammal ancestor was likely a heterotherm, we explored the potential for heterothermy in a primate closely related to the Strepsirrhini. Based upon phylogeny, body size and habitat stability since the Late Eocene, we selected western tarsiers (Cephalopachus bancanus) from the island of Borneo. Being the sister clade to Strepsirrhini and basal in Haplorrhini (monkeys and apes), we hypothesized that C. bancanus might have retained the heterothermic capacity observed in several small strepsirrhines. We measured resting metabolic rate, subcutaneous temperature, evaporative water loss and the percentage of heat dissipated through evaporation, at ambient temperatures between 22 - 35°C in fresh-caught wild animals (126.1 ± 2.4g). We also measured core body temperatures in free-ranging animals. The thermoneutral zone was 25 - 30°C and the basal metabolic rate was 3.52 ± 0.06 W.kg-1 (0.65 ± 0.01ml O2.g-1.hr-1). There was no evidence of adaptive heterothermy in either the laboratory data or the free-ranging data. Instead, animals appeared to be cold sensitive (Tb 31°C) at the lowest temperatures. We discuss possible reasons for the apparent lack of heterothermy in tarsiers, and identify putative heterotherms within Platyrrhini. We also document our concern for the vulnerability of C. bancanus to future temperature increases associated with global warming.